THE FISHBONE METHOD AS ONE OF THE TOOLS FOR CRITICAL THINKING DEVELOPMENT IN HIGHER EDUCATION STUDENTS DURING THE STUDY OF THE EDUCATIONAL COMPONENT “MICROBIOLOGY, VIROLOGY, AND IMMUNOLOGY” - Zviaholska, Iryna; Derevyanko, Tetiana; Polianska, Valentyna (Eastern Ukrainian Medical Journal, 2024)
Introduction. One of the primary objectives in training the new generation of specialists within the post-non-classical educational paradigm is to accelerate the development of critical thinking through interactive learning technologies. In the updated educational environment of the Department of Microbiology, Virology, and Immunology at Poltava State Medical University, fostering creative aptitudes promises significant benefits for both general personal growth and specialized professional preparation, which is particularly crucial for future doctors. Among the innovative tools for cultivating critical thinking skills, the Fishbone method stands out as a practical opportunity for integration into the educational process. This research aims to highlight and analyze the implementation of the Fishbone method as a means of fostering critical thinking among students during practical sessions in the course "Microbiology, Virology, and Immunology" at Poltava State Medical University. By using this institution as a case study, the study seeks to demonstrate the method’s effectiveness in enhancing students’ analytical abilities and preparing them for the complexities of their future professional roles. Discussion. The authors employ general scientific methods of theoretical inquiry to substantiate the importance and development trajectories of critical thinking among higher education students, emphasizing its role as an integral component in training future specialists of the new generation. The study underscores that fostering critical thinking in contemporary educational landscapes requires embracing a holistic post-non-classical educational paradigm and innovative methodological approaches. Within this framework, the authors examine the feasibility of integrating the Fishbone method into the educational environment of the Department of Microbiology, Virology, and Immunology at Poltava State Medical University. The authors outline the Fishbone method, highlighting its universal applicability and proposing various strategies for its integration into the educational process. By detailing the method’s practical implementation in specific practical sessions and offering a catalog of recommended lesson topics suitable for its use, the article provides a comprehensive framework for its adoption. The implementation of the Fishbone method is expected to enhance students’ intellectual engagement, spark a thirst for knowledge, enable critical appraisal of information, and facilitate the identification of key points from vast amounts of data. It also aids in transforming analyzed data into compelling ideas and honing the ability to discern causal relationships, visually reinforced through diagrams. Moreover, this method is instrumental in cultivating soft skills and imparting a research-oriented character to certain educational stages. Through these innovations, students are better prepared to navigate complex educational settings and develop into well-rounded professionals. The authors emphasize the essential role of teachers with modern professional competencies in fostering effective collaboration among all stakeholders in the educational and cognitive process. The article argues that adopting innovative pedagogical technologies not only enhances the quality of the "subject-subject" partnership and promotes the acquisition of key competencies but also significantly contributes to the development of students’ professional and personal attributes and propaedeutic thinking. This approach ultimately leads to a more holistic and effective educational experience, preparing students to excel in their future careers. Conclusions. The implementation of the Fishbone method in the study of "Microbiology, Virology, and Immunology" has proven to be both feasible and effective as a modern educational technology. This structured approach encourages students to engage deeply with scientific and informational content, prompting critical analysis and fostering intellectual autonomy. By using the Fishbone method, educators can stimulate students’ capacity for independent thought and enhance their ability to communicate effectively within the discipline. This method not only promotes creative collaboration but also equips students with the skills necessary to navigate uncertainties and devise solutions in educational settings. Ultimately, it lays a solid foundation for their future academic and professional endeavors.